Reconstructing Islamic Religious Education through the Experiential Learning Cycle at Sanggar Anak Alam (SALAM) - Sakana Tiswi Miswala; Mohammad Zakki Azani (MASI Mandiri Edukasi, 2026)
This study examines the gap between the normative purpose of Islamic Religious Education and its empirical reality in educational practice. Although Islamic Religious Education is intended to shape students’ character and encourage the practice of religious values in daily life, moral degradation, violence, and weak value internalization are still found in educational settings, including Islamic-based schools. This study focuses on understanding the process of value internalization in the experiential learning cycle at Sanggar Anak Alam (SALAM) Yogyakarta and its relevance to the reconstruction of Islamic Religious Education methods. Using a qualitative case study approach, this research combines field research and library research. Data were collected through semi-structured interviews with two senior SALAM facilitators, direct observation, and document analysis. The findings show that SALAM offers important pedagogical insights through experiential and dialogical learning, reflective and process-based evaluation, and the facilitator’s role in guiding students’ learning process. Through these aspects, value internalization takes place not only at the level of understanding, but also through experience, reflection, dialogue, and real action in everyday life. This study contributes a pedagogical reflection on how Islamic Religious Education may incorporate more reflective, participatory, and experience-based approaches in supporting value internalization, moving beyond cognitive and one-way learning models.